Belinostat for the treatment of relapsed or refractory peripheral T-cell lymphoma. (March 2017) - Campbell, Peter; Thomas, Christan M
Peripheral T-cell lymphoma is a heterogenous non-Hodgkin Lymphoma with historically poor outcomes. Currently, response rates remain poor with traditional chemotherapy and many of those responding to initial therapy will relapse. Belinostat (Beleodaq, Spectrum Pharmaceuticals) is a histone deacetylase inhibitor (HDACi) approved for use in relapsed or refractory peripheral T-cell lymphoma (PTCL). Belinostat is metabolized hepatically through cytochrome P-450 enzymes 3A4, 2C9, and 2A6; however, no empiric dosage adjustments of belinostat are recommended during concurrent use of inhibitors or inducers of these enzymes. Belinostat's efficacy has been evaluated in a clinical trial showing an overall response rate (ORR) of 25.8% and a median duration of response of 8.4 months. Belinostat is generally well tolerated, with the most common adverse reactions (>25%) being nausea, vomiting, fatigue, pyrexia, and anemia in patients with relapsed or refractory PTCL. Belinostat is a safe and effective treatment option for relapsed and refractory peripheral T-cell lymphoma, with many future applications currently being investigated.